PEMANFAATAN SUMBER MATA AIR SEBAGAI KEBUTUHAN PENDUDUK - Siska Marviyanasari; I Gede Sugiyanta; Irma Lusi Nugraheni (JPG (Jurnal Penelitian Geografi), 2013)
Abstract: This study aimed to examine the use and quality of water that comes from springs as the needs of the population in the Village District Wonoharjo Sumberejo Tanggamus district of Lampung Province in 2012. The method used is descriptive method with the object of study is three springs in the village located in the hamlet Wonoharjo I (Sriwidodo), Hamlet II (Sridadi), and Hamlet III (Murtirejo). Taking Patriarch done proportionally random sampling. Data collection techniques are observation, interview techniques, and technical documentation. Residents use water that comes from springs for drinking, cooking, bathing, washing clothes, washing utensils, water, irrigation and agriculture, livestock and fisheries. The results of water quality showed that: 1) All springs odorless, turbid, and colorless. 2) TDS on springs I is 47 mg/l, springs II is 102mg/l, and springs III is 112m /l. 3) Sense of the spring I and spring II is sour, while the springs III is not sour. 4) The temperature of the spring I and spring II is 28°C, springs III reached 29°C. Water quality by chemicals, namely: 1) pH spring I and spring II is 5.77 mg/l, springs III is 6.21 mg/l. Biological water quality, namely: 1) BOD spring I was 69.894 mg/l, springs II was 70.891 mg/l, springs III is 73.308 mg/l, 2) COD spring I was 0 mg/l, springs II was 94.144 mg/l, and springs III is 70.608 mg/l. The results showed that water use: 1) Used for drinking water, cooking, bathing, washing clothes, washing utensils, 100%. 2) Livestock are 4 households is 11.11%. 3) Water irrigation and agriculture amounted to 26 is 72.22%. 4) Livestock ie 4 ie 11.11%. 5) there are 6 Fishing is 16.67%. Key words: Utilization of Water, Springs, Water Quality